Stress–strain relationship of rubberized geopolymer concrete with slag and fly ash - Azunna, Sunday U.; Aziz, Farah N.A.A.; Rashid, Raizal S.M.; Mahsum, Ernaleza (Multidisciplinary Digital Publishing Institute, 2025)
Rubberized concrete is a more environmentally friendly material than natural concrete as it helps to reduce rubber disposal issues and has superior impact resistance. Geopolymer concrete, on the other hand, is an economical concrete with higher mechanical properties than nominal concrete that uses fly ash and slag, among other industrial solid wastes, to lower carbon footprints. Rubberized geopolymer concrete (RuGPC) combines the advantages of both concrete types, and a thorough grasp of its dynamic compressive characteristics is necessary for its use in components linked to impact resistance. Despite the advantages of RuGPC, predicting its mechanical characteristics is sometimes difficult because of variations in binder type and combination. This research investigated the combined effect of ground granulated blast furnace slag (GGBFS) and fly ash (FA) on the workability, compressive strength, and stress–strain characteristics of RuGPC with rubber at 0%, 10%, and 20% fine aggregate replacement. Thereafter, energy absorption and ductile characteristics were evaluated through the concrete toughness and ductility index. Numerical models were proposed for the cube compressive strength, modulus of elasticity, and peak strain of RuGPC at different percentages of crumb rubber. It was found that RuGPC made with GGBFS/FA had similar stress–strain characteristics to FA- and MK-based RuGPC. At 20% of crumb rubber aggregate replacement, the workability, compressive strength, modulus of elasticity, and peak stress of RuGPC reduced by 8.33%, 34.67%, 43.42%, and 44.97%, while Poisson’s ratio, peak, and ultimate strain increased by 30.34%, 8.56%, and 55.84%, respectively. The concrete toughness and ductility index increased by 22.4% and 156.67%. The proposed model’s calculated results, with R2 values of 0.9508, 0.9935, and 0.9762, show high consistency with the experimental data. RuGPC demonstrates high energy absorption capacity, making it a suitable construction material for structures requiring high-impact resistance.